Demystifying customer satisfaction towards an authorised automobile service centre / Cho Sin Win...[et al.] - Cho, Sin Win; Md Isa, Normalisa; Salahuddin, Norkhazzaina; Sivapathy, Arunnaa; Ramlee, Afifah Alwani (Universiti Teknologi MARA, Kedah, 2019)
Understanding and sustaining customer satisfaction is vital and challenging specifically in the automobile service industry. Therefore, the present study aims to identify factors influencing customer satisfaction towards the automobile service center. SERVQUAL instrument was adapted and more than 380 questionnaires were distributed to the respondents who had experience visiting the automobile service center in the northern region of Malaysia. The result of the study showed there is a significant relationship between service quality and customer satisfaction where it has explained about 48% of the variation in customer satisfaction. Empathy, reliability, responsiveness, and assurance were found to be important factors in influencing customer satisfaction.